Identifikasi Sektor Unggulan Pada Perekonomian Kabupaten Hulu Sungai Tengah: Analisis Input-Output - Rakhman, Rizaldi; Imansyah , Muhammad Handry (PPJP ULM, 2021)
The development of a sector requires a lot of funds. The allocation of funds owned makes which sectors are prioritized something that must be resolved. So that it can channel existing funds to superior sectors effectively. This study aims to determine the superior sector of Hulu Sungai Tengah Regency. There are 3 methods used, namely Linkage Analysis, Distribution Impact and Multiplier Analysis which is divided into several techniques. In addition, the Input-Output Table used is the result of the 2010 South Kalimantan Province Input-Output Table which was derived using the Location Qoutient and updated to the latest year so that the Input-Output Table of Hulu Sungai Tengah Regency 2018 is obtained. The results of this study from each analysis technique differed from one another after adjusting. The results show that Hulu Sungai Tengah District still depends on the agricultural sector, which is not a leading sector.